A facile in-situ polymerization strategy towards polyimide/carbon black composites as high performance lithium ion battery cathodes. (10th January 2018) - Zhang, Guangfeng; Xu, Zhixiao; Liu, Ping; Su, Yuezeng; Huang, Tao; Liu, Ruili; Xi, Xin; Wu, Dongqing
Abstract: In this work, a facial in-situ polymerization strategy is developed for the first time to fabricate the composites of polyimide and carbon black (PI/CBs) by the condensation of 1, 2, 4, 5-benzenetetracarboxylic anhydride and p -phenylenediamine with the presence of carbon black. This composition method can effectively suppress the crystallization of PI and thus allows the sufficient contact of PI and carbon black. As the cathode material in LIBs, the PI/CB composite manifests an extraordinary capacity of 182 mAh g −1 at 0.1 A g −1, close to the theoretical value of PI. Moreover, the capacity of the PI/CB composite can be retained as 116 m Ah g −1 even at an ultrahigh current density of 10 A g −1, outperforming the recently reported polymer LIB cathodes. Under the same conditions, the mechanical mixture of highly crystallized PI sheets and carbon black shows a much poorer performance. The approach demonstrated herein is expected to be further applied as an effective processing method to build up high performance electrodes with organic species in secondary batteries. Graphical abstract: An in-situ polymerization strategy is utilized to fabricate the composites of polyimide and carbon black (PI/CBs) by the condensation of 1, 2, 4, 5-benzenetetracarboxylic anhydride and p -phenylenediamine with the presence of carbon black. As the cathode material in LIBs, the PI/CB composite manifests an extraordinary capacity of 182 mAh g −1 at 0.1 A g −1, which can be retained as 116 m Ah g −1 even at 10 A g −1 .